Pendidikan Inklusif dan Multikultur dalam Perspektif Hadis Nabi Saw - Chaer, Moh Toriqul (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2016)
Â The study of the association or social interaction in Islamic education serves as the urgent problembecausea good social interaction is likely to affectstudentsâ good behavior in a pluralistic society and religious culture. Studentsâ understanding of this substance has become a very important resource in instilling the inclusive and multicultural education. This article presented and examined the hadiths which were relevant to Islamic educational materialsregarding the instructional issues of social interaction, tolerance, and cooperation such as Muamalah rights and Islamic preaching. The study revealed that the hadiths related to social interaction with non-Muslims had notrecommended to be rude to the non-Muslims if they did not hurt and harm the Muslims. This is consistent with the meaning of Islam itself that is to save and is not to be a device that punishthe people who do not believe in Allah, and Islam should be the spirit of unlimited ocean full of love who is able to frame the diversity in Indonesia.Ø¥Ù Ø¯Ø±Ø§Ø³Ø© Ø§ÙØµÙØ© Ø§ÙØ§Ø¬ØªÙØ§Ø¹ÙØ© ÙÙ Ø¹Ø§ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙÙÙØ©Ø ÙØ£Ù Ø§ÙØµÙØ© Ø§ÙØ§Ø¬ØªÙØ§Ø¹ÙØ© Ø§ÙØ·ÙÙØ¨Ø©Â  ØªØ¤Ø¯ÙÙ Ø¥ÙÙ Ø§ÙØ³ÙÙÙ Ø§ÙØØ³Ù ÙÙØ·ÙØ§Ø¨ ÙÙ Ø§ÙÙØ¬ØªÙØ¹ Ø§ÙÙØªØ¹Ø¯Ø¯ Ø§ÙØ«ÙØ§ÙØ§Øª ÙØ§ÙØ£Ø¯ÙØ§Ù. ÙØ¥Ù ÙÙÙ Ø§ÙØ·ÙØ§Ø¨ ÙÙØ°Ù Ø£ØµØ¨Ø ÙØ§Ø¯Ø© ÙÙÙØ©Â  ÙÙ Ø¶ÙØ¡ ØºØ±Ø³ ÙÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ´Ø§ÙÙØ©Â  ÙØ§ÙÙØªØ¹Ø¯Ø¯Ø© Ø§ÙØ«ÙØ§ÙØ§Øª. ØØ§ÙÙØª ÙØ°Ù Ø§ÙÙÙØ§ÙØ© Ø¹Ø±Ø¶ Ø§ÙØ£ØØ§Ø¯ÙØ« Ø§ÙÙÙØ§Ø³Ø¨Ø© Ø¨ÙÙØ§Ø¯ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø§ÙÙØªØ¹ÙÙØ© Ø¨Ø§ÙØ§ØªØµØ§Ù Ø§ÙØ§Ø¬ØªÙØ§Ø¹Ù ÙØ§ÙØªØ³Ø§ÙØ ÙØ§ÙØªØ¹Ø§ÙÙØ ÙØ«Ù Ø§ÙØ£ØØ§Ø¯ÙØ« Ø¹Ù ØÙÙÙ Ø§ÙÙØ¹Ø§ÙÙØ© ÙØ§ÙØ¯Ø¹ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ©.Â  ÙØ«ÙØ© Ø£ØØ§Ø¯ÙØ« ÙØªØ¹ÙÙØ© Ø¨Ø§ÙØ§ØªØµØ§Ù Ø§ÙØ§Ø¬ØªÙØ§Ø¹Ù Ø¨ØºÙØ± Ø§ÙÙØ³ÙÙÙÙ, ÙØ£Ø´Ø§Ø±Øª Ø§ÙØ£ØØ§Ø¯ÙØ« Ø¥ÙÙ Ø£ÙÙÙ ÙÙØ³ ÙÙØ§Ù ØØ«Ù Ø¹ÙÙ Ø¥ÙØ°Ø§Ø¡ ØºÙØ± Ø§ÙÙØ³ÙÙÙÙ Ø¥Ø°Ø§ ÙØ§ÙÙØ§ ÙØ§ ÙØ¤Ø°ÙÙ Ø§ÙÙØ³ÙÙÙÙ ÙÙØ§ ÙØ¶Ø±ÙÙÙÙÙ. ÙÙØ°Ø§ ÙÙØ§ ÙÙØ¬Ø¯ ÙÙ ÙØ¹ÙÙ Ø§ÙØ¥Ø³ÙØ§Ù (Ø§ÙÙÙØ¬ÙÙ) ÙÙÙØ³ Ø¬ÙØ§Ø²Ø§ ÙØªØÙÙÙ Ø¬ÙÙØ¹ Ø§ÙÙØ§Ø³ Ø§ÙØ°ÙÙ ÙØ§ ÙØ¤ÙÙÙÙ Ø¨ÙØ ÙÙÙ ÙÙÙÙ ÙØ§Ø´Ø±Ø§ ÙØ±ÙØ Ø§ÙÙØØ¨ÙØ© ÙØ¬ÙÙØ¹ Ø§ÙÙØ§Ø³ ÙÙ Ø¶ÙØ¡ Ø§ÙØªØ¹Ø¯ÙØ¯Ø§Øª ÙÙ Ø¥ÙØ¯ÙÙÙØ³ÙØ§.